Fluctuations Analysis Total Electricity Consumption of Households in the year 2005-2006 by Using Average Deviation and Standard Deviation - Ambar Ari Astuti (Jurnal Sistem Informasi, 2007)
Average deviation and standard deviation measures included in the distribution of absolute (absolute dispersion), and is one measure of knowledge of the statistics used to describe a set of data that has been made or not made with attention to every value in the corresponding data set.The figures produced in the calculations using the average deviation and standard deviation expressed in the same units as the original data units.